(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective: Dengue hemorrhagic fever is a disease transmitted by the mosquito Aedes aegypti. Prevention of transmission of this disease one of which is the chemical control with temefos, but the use of sustainable temefos can cause insect resistance and environmental damage. Therefore we need an effective and safe alternative to larvicide, the suspension of Bacillus thuringiensis var israelensis. Methods: This study used a type of true experimental research design with posttest only control group design. Samples used in this study are the third instar larvae of Aedes aegypti. Concentrations used in this study were a 0.01%; Of 0.02%; Of 0.03%; 0:04% and 0.05% by the number of 25 larvae per treatment and 3 times replication. Results: Based on the Kruskal Walls obtained a value of 0.009> 0.05 means there is a stock mortality of larvae using a suspension of the bacterium Bacillus thuringiensis, temefos and distilled. Test Mann Whitney showed that among the positive control (temefos a 0.01%) and negative control (distilled water) there are differences in the number of larvae mortality significantly, the positive control treatment with no significant difference, and between negative control and treatments armpits there are differences in the number of deaths larvae significant. The LC50 value obtained was 0.010% and the LT50 value obtained was 2,683 hours. Conclusions: The suspension of bacteria Bacillus thuringiensis is effective in killing the larvae of Aedes aegypti with LC50 values of 0.0105 and LT50 values on the clock to 2.683. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.706-710